Réponses

Meilleure réponse !
  • Utilisateur Brainly
2013-04-20T15:54:03+02:00

3x+2=x+6

3x+2-x=x+6-x

2x+2=+6

2x+2-2=+6-2

2x=4

x=4/2

x=2

 

-8x+3=5x-2

-8x+3-5x=5x-2-5x

-13x+3=-2

-13x+3-3=-2-3

-13x=-5

x=-5/-13

 

voilà...... :)

2013-04-20T16:18:33+02:00

3x+2=x+6

3x+2-x=x+6-x

2x+2=+6

2x+2-2=+6-2

2x=4

x=4/2

x=2

 

verficication¨:

(3x2)+2=2+6

6+2=2+6

 

-8x+3=5x-2

-8x+3-5x=5x-2-5x

-13x+3=-2

-13x+3-3=-2-3

-13x=-5

x=5/13

 

verification:

(-8x5/13)+3=(5x5/13)-2

-40/13+3=25/13-2

-40/13+39/13= 25/13-26/13

-1/13=-1/13